Anti-tumour necrosis factor therapy for early-stage Dupuytren's disease (RIDD): a phase 2b, randomised, double-blind, placebo-controlled trial. (June 2022) - Nanchahal, Jagdeep; Ball, Catherine; Rombach, Ines; Williams, Lynn; Kenealy, Nicola; Dakin, Helen; O'Connor, Heather; Davidson, Dominique; Werker, Paul; Dutton, Susan J; Feldmann, Marc; Lamb, Sarah E
Summary: Background: Dupuytren's disease is a common fibrotic condition that causes the fingers to flex irreversibly into the palm. Treatments for late-stage disease all have limitations, and there is no approved treatment for early-stage disease. We identified tumour necrosis factor as a therapeutic target in Dupuytren's disease, and in a dose ranging trial found 40 mg adalimumab in 0·4 mL to be most efficacious. Here we aimed to assess the effects of intranodular injection of adalimumab in early-stage disease. Methods: In this phase 2b, randomised, double-blind, placebo-controlled trial adults with early-stage Dupuytren's disease and an established clinically distinct nodule with a clear history of progression in the preceding 6 months were recruited from two clinical centres in the UK and were randomly assigned 1:1 to receive four injections of adalimumab or saline every 3 months. Participants and assessors were masked. The primary outcome was nodule hardness measured with a durometer at 12 months. Data were analysed by linear mixed effects regression models in the intention-to-treat population with multiple imputation for missing primary outcome data. The trial is registered at the ISRCTN registry, ISRCTN 27786905 and is complete. Findings: Between Feb 17, 2017, and Jan 11, 2019, 284 participants were screened in the UK and 140 were enrolled. 47 (34%) participants were female and 93 (66%) were male. Mean age of participants was 59·7 years (SD 10·0). Primary outcome data were available from 113 participants. Nodule hardness was lower (−4·6 AU [95% CI −7·1 to −2·2], p=0·0002) in the adalimumab compared with the saline group at 12 months. There were no related serious adverse events; the most common adverse events were minor injection site reactions. Interpretation: Intranodular injections of adalimumab in participants with early-stage Dupuytren's disease resulted in softening and reduction in size of the nodules. Longer follow-up would be required to assess the effect of tumour necrosis factor inhibition on disease progression, extension deficit and hand function. Funding: Health Innovation Challenge Fund (Wellcome Trust, Department of Health) and 180 Life Sciences.